Periodontal management of amlodipine-induced gingival hyperplasia in a hypertensive patient: A surgical approach - Houda El Ayachi; Oum Keltoum Ennibi (Wolters Kluwer Medknow Publications, 2021)
Background: Amlodipine is a third-generation dihydropyridine calcium channel blocker used to treat hypertension and angina. Gingival hyperplasia (GH) is an unwanted side effect associated with this therapy. It causes unsatisfactory esthetics, difficulty in maintaining good oral hygiene, abnormal tooth movement, and difficulty in mastication. GH can be managed by nonsurgical therapy alone or using a combination of nonsurgical and surgical therapy. Case Report: A 55-year-old female patient came to the clinical department of periodontology, University Hospital of Rabat, with a chief complaint of gingival enlargement. It was diagnosed and initially managed by nonsurgical periodontal treatment. Drug substitution and surgical intervention were executed. Regular supportive periodontal therapy showed a good and stable outcome over 2 years of follow-up. Conclusion: Amlodipine-induced GH can be managed using periodontal procedures combined with good oral hygiene and regular supportive periodontal therapy.